Job Stress and Work Performance: Evidence of Female Employees of Banks in Rupandehi District - Rayamajhi Sushma (Journal of Corporate Finance Management and Banking System, 2024)
The study's goal is to discover the factors that contribute to stress and the impact of stress on work performance in the banking industry. This study also gives data on the employees' degree of stress and level of performance. For the research project, 16 banks from the Rupendehi district were taken as sample employed and non-probability sampling was used to generate a representative sample. The sample size was 386 respondents. Respondents' main data were collected via a questionnaire. Regression analysis, correlation, and oneway ANOVA. The study's findings show that job-related stress, peer support, and work-life balance have a substantial influence on employee performance in the banking industry. The study also concludes that Organizational Stress Factors have no substantial influence on employee performance.